Analisis SWOT Program Studi Desain Komunikasi Visual Universitas Ma Chung untuk Merumuskan Grand Strategy dan Pertimbangan Penyusunan Kurikulum DKV - Aditya Nirwana; Nathania Maharani Lynn Handoko (MAVIS : Jurnal Desain Komunikasi Visual, 2021)
SWOT analysis is the first step for the preparation of higher education curricula, namely assessing the strengths, weaknesses, opportunities and threats faced by institutions of higher education, in this case the Visual Communication Design Study Program of Ma Chung University . The purpose of this SWOT analysis is to find the formulation of the strategy of the Visual Communication Design Study Program at Ma Chung University in the form of: 1) Grand strategy; 2) Determination of the main objectives of the grand strategy, 3) Description of internal and external factors and 4) Suggestions for curriculum development in relation to the organization's grand strategy. By using both quantitative and qualitative methods (mix methods) the results of the strategy are obtained: 1) The use and strengthening of Blended Learning-OBE learning development; 2) Improving the strategic management of the study program, 3) Reorganizing academic administration at the level of the study program with formal, clear and certain procedures; 4) Give more attention to the method of learning field studies, 5) Establish cooperation with various partners both industry, in terms of sharing infrastructure and facilities; 6) Use of open source software; 7) Guest lectures that prioritize graduates / alumni; 8) Sharpen again, while evaluating Field Work Practices in the freelancer mode; and 9) Updating the concentration of studies; and 10) Prioritizing group activities to improve teamwork.